IDENTIFIKASI CENDAWAN ENTOMOPATOGEN BEAUVERIA SPP. YANG MENGINFEKSI SERANGGA HAMA PADA PERTANAMAN PADI SAWAH - Paradillah Ilyas Mattola; Muh Yusuf Idris (Journal TABARO Agriculture Science, 2022)
The purpose of this study is to explore, isolate and identify the entomopathogenic mushroom Beauveria spp that infects the pests in wild peas plantations. The research was carried out by taking samples of pests infected with entomopatogen mushrooms in peas plants. On the plants diagrams nine U-like sample points were determined. Each sample point consisted of 30 pests. Observations began 57 days after planting up to 99 days following planting with sampling every week. The samples were isolated into the Potato Dextrose media to be identified. The results of the research were that the isolated entomogenic fungus Beauvera spp. was found in pests Leptocorisa orus, six insulators Beauver and sppia. Two isolators were found in Schirophirp innotaga